Analysis of the Management of Cereal Crop Residues on Farms to Optimise Cattle Feed in the Western Cotton Growing Zone of Burkina Faso - Adama, Belem; Salifou, Ouédraogo-Koné; Bazoumana, Koulibaly; Dramane, Traoré; Mamadou, Traoré (Journal of Agricultural Studies, 2024)
Crop residues are insufficiently valorised by farmers in western Burkina Faso, while cattle face a shortage of forage. The aim of this study was to analyse the management of cereal crop residues in cotton-cereal farming to optimise their use as feed for draught cattle. A sample of 72 cotton farmers was selected from nine villages in the study area by the stratification method and interviewed using a semi-structured questionnaire. The quantities of cereal crop residue biomass collected by farmers were assessed directly in the field. The results showed that maize and sorghum stalks were predominantly used in cattle feed (86.1 and 90.3%), composting (50 and 44.4%), and mulching (26.9 and 25%), respectively. The average quantities of cereal crop residues stored were 0.83, 0.16, and 1.19 tonnes of dry matter (tDM) for crop farmers, livestock breeders, and agro-pastoralists, respectively, with respective fodder balances of -3.99, -29.05, and -16.99 Tropical Cattle Units (TCU) for the use of cattle, or -0.88, -0.38, and -1.81 TCU for the use of draught cattle during the lean season. Concentrated feed use was 0.20, 0.05, and 0.21 kg/cattle/day; respectively. The main factors influencing the quantities of cereal residues stored on the farms were the size of the cultivated areas and the farmers’ capacity for transportation. Provision of transport equipment and storage infrastructure would therefore appear to be a solution that could improve the level of fodder residue storage, particularly for draught oxen.